Hubungan antara Organisasi Kemahasiswaan dan Indeks Prestasi yang Dimoderasi oleh Manajemen Waktu. - Wanwan Jamaludin; Pasha Azqyansyah; Adi Gunawan; Fakhru Husaeni (Civiliza Publishing, Indonesia., 2026)
This study aims to analyze the relationship between student organizations and students' Grade Point Average (GPA) with time management as a moderating variable. The research is motivated by the differences in previous research results regarding the influence of organizational activity on academic achievement and the limited research that examines the moderating role of time management. The study used a quantitative approach with a purposive sampling technique on 93 active students of the Wastukancana Purwakarta College of Technology who had participated in student organizations for at least one semester. Data were collected through a Likert scale questionnaire and analyzed using PROCESS Macro Hayes Model 1. The research hypotheses include the influence of student organizations on GPA, the influence of time management on GPA, and the moderating role of time management. The results showed that neither student organizations nor time management had a direct effect on GPA. However, the interaction between student organizations and time management proved to have a significant effect, so that time management acted as a moderating variable that changed the direction and strength of the relationship between student organizations and GPA. These findings contribute to the development of student behavior studies by demonstrating the importance of time management skills in maintaining a balance between organizational activities and academic achievement.